2015
DOI: 10.1371/journal.pone.0141689
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pregnancy-Related Deaths on Female Life Expectancy in Zambia: Application of Life Table Techniques to Census Data

Abstract: IntroductionSince 2000, the world has been coalesced around efforts to reduce maternal mortality. However, few studies have estimated the significance of eliminating maternal deaths on female life expectancy. We estimated, based on census data, the potential gains in female life expectancy assuming complete elimination of pregnancy-related mortality in Zambia.MethodsWe used data on all-cause and pregnancy-related deaths of females aged 15–49 reported in the Zambia 2010 census, and evaluated, adjusted and smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 30 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…The eighteen included studies were primarily hospital or health clinic based patient record reviews, except for two studies which were based on household surveys [ 16 , 17 ], one which was based on public death notification forms [ 18 ], and one which used various data sources [ 19 ]. Two of the studies, both by Mombo-Ngoma et al, reported on some of the same data [ 20 , 21 ], and to avoid adding the same data twice, only one of the studies was included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The eighteen included studies were primarily hospital or health clinic based patient record reviews, except for two studies which were based on household surveys [ 16 , 17 ], one which was based on public death notification forms [ 18 ], and one which used various data sources [ 19 ]. Two of the studies, both by Mombo-Ngoma et al, reported on some of the same data [ 20 , 21 ], and to avoid adding the same data twice, only one of the studies was included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies had data on adolescents aged less than 15 years [ 16 , 18 , 19 ], four studies had an adolescent group aged 15 years or less [ 22 25 ], five studies included adolescents aged 16 years or less [ 20 , 21 , 26 28 ], while six included adolescents up to 17 years old [ 17 , 29 34 ]. There were three studies from Cameroon [ 23 , 27 , 28 ], two each from Nigeria[ 25 , 29 ], Tanzania [ 24 , 32 ], South Africa [ 18 , 34 ] and Zambia [ 16 , 17 ], one study each from Namibia [ 31 ], Gabon [ 20 ], Ghana [ 33 ], Ethiopia [ 19 ] and Sudan [ 26 ], and two multi-country studies: Ganchimeg et al with data from Algeria, Angola, Democratic Republic of Congo, Niger, Nigeria, Kenya and Uganda [ 22 ], and Mombo-Ngoma et al which included data from Benin, Gabon and Mozambique [ 21 ]. See Table 2 for study characteristics, and Tables 3 and 4 for results for the individual studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations